2020
DOI: 10.5530/pj.2020.12.159
|View full text |Cite
|
Sign up to set email alerts
|

Prototype Star Fruit-Honey Product and Effectiveness on Antixidants, Inflammation and Walking Distance in Participants with Stable Chronic Obstructive Pulmonary Disease (COPD)

Abstract: Background: Star fruit (Averrhoa carambola L.) is a seasonal fruit, which has proven antioxidant and inflammation activities in vitro. However, sweet-type is more available than sour-type. Therefore, developing a new product from sweet-type star fruit, and evaluating its effectiveness on antioxidants and inflammation have been very challenging. Objectives: The aims were to develop a prototype product from sweet-type star fruit and evaluate its effectiveness with or without walking exercise on participants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 77 publications
(95 reference statements)
3
16
0
Order By: Relevance
“…39 Thus, the results in this study showed the pro-oxidation activity of SF sour-type and antioxidant activity of sweet-type in in vitro models. Thus, the results in this study supported previous studies in which participants who had chronic obstructive pulmonary disease (COPD) 10 stabilized with antioxidant activity in sweet-type SF. However, the benefits of sour-type SF must be considered and need to be studied further.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…39 Thus, the results in this study showed the pro-oxidation activity of SF sour-type and antioxidant activity of sweet-type in in vitro models. Thus, the results in this study supported previous studies in which participants who had chronic obstructive pulmonary disease (COPD) 10 stabilized with antioxidant activity in sweet-type SF. However, the benefits of sour-type SF must be considered and need to be studied further.…”
Section: Discussionsupporting
confidence: 91%
“…This study was an updated and a confirmed work of SF distributed in Thailand, 9,10 and it also supports a previous study on elderly people. 8,20 The results in this study represented active compounds such as phenolics and Vit C is the same as in the previous evidence from the data.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Contamination from yeast, fungi [36], microbial pathogens, especially coliforms, Escherichia coli, yeast, fungi, Salmonela sp, Clostridium perfringens, Staphylocossus aureus and Bacillus cereus, placed under a compendium of methods for food analysis [37], was approved with a food serial number of 50-1-02237-2-0122. Moreove, possible toxicity from oxalic acid content in the SF product in this study, which may affect neurotoxic or neuphrotoxic conditions [38] was rechecked as in the previous study [29]. Previous evidence reported that a minimal dose of 4-5 grams of oxalate caused death in adults [39].…”
Section: [Table Insert] Discussionmentioning
confidence: 64%
“…Updated evidence on sweet-type SF extract showed activities on radical scavenging as well as suppressed in ammation through inhibiting TNF-∝ in vitro [26]. Thus, the new product of sweet-type SF was very challenging at the industrial level as in previous study [29]. The SF product was prepared similarly under the guideline of the Department of Public Health, Thailand, before being approved for the study of people with COPD in that study and in a community of elderly people in this study.…”
Section: [Table Insert] Discussionmentioning
confidence: 94%